2010
DOI: 10.1515/hf.2010.033
|View full text |Cite
|
Sign up to set email alerts
|

Thermal aging of 1-alkyl-3-methylimidazolium ionic liquids and its effect on dissolved cellulose

Abstract: The thermal degradation products of 1-alkyl-3-methyl-imidazolium-type ionic liquids (e.g., BMIM, EMIM), which are commonly used in cellulose chemistry, were identified. Imidazole (5), N-methylimidazole (6), and N-alkylimidazoles (7, 8) are the main products. Moreover, dimeric substituted imidazoles (9–11) were found carrying a methylene bridge formed from the N-methyl structure. The former 1-alkyl group (butyl or ethyl) was not present in any of the dimeric compounds. The N-methylene intermediate (12) acts as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
38
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(39 citation statements)
references
References 13 publications
1
38
0
Order By: Relevance
“…For example, the dialkylimidazolium cation can show trans-alkylation, resulting in a symmetrical dialkylimidazolium structure, or undergo elimination or retro-alkylation, causing liberation of one alkyl residue and concomitant formation of an alkylimidazole [110,111]. Similar reactions were observed in a detailed study by Liebner et al, who, in addition to the aforementioned products, also identified methylene-bridged imidazole dimers [112]. The basic amine products can act as catalysts for further degradation reactions or induce secondary side reactions such as deprotonation of the imidazolium C2-H proton, resulting in carbene formation [113].…”
Section: Thermal Degradation Of the Cellulose-il Systemsupporting
confidence: 67%
“…For example, the dialkylimidazolium cation can show trans-alkylation, resulting in a symmetrical dialkylimidazolium structure, or undergo elimination or retro-alkylation, causing liberation of one alkyl residue and concomitant formation of an alkylimidazole [110,111]. Similar reactions were observed in a detailed study by Liebner et al, who, in addition to the aforementioned products, also identified methylene-bridged imidazole dimers [112]. The basic amine products can act as catalysts for further degradation reactions or induce secondary side reactions such as deprotonation of the imidazolium C2-H proton, resulting in carbene formation [113].…”
Section: Thermal Degradation Of the Cellulose-il Systemsupporting
confidence: 67%
“…However, our system does not contain cyanamide groups. On the other hand, a nice paper reported by Liebner et al [27] on thermal degradation studies of 1-alkyl-3-methyl imidazolium ILs suggests the formation of imidazole, N-alkylimidazoles and dimeric compounds constituted by two imidazole moieties linked by a methylene bridge. Such decomposition products are relatively strong bases.…”
Section: Characterization Of the Epoxy Pre-polymer/il Binary Blendsmentioning
confidence: 99%
“…Highest stabilities are obtained in pure ILs from which degradation productions had previously been removed (Liebner et al 2010). Acidic degradation products, such as acetic acid, gluconic acid from cellulose or 2-furancarboxylic acid from xylan, generally destabilize NMMO, whereas basic degradation products, such as 1-methylimidazole from the IL (Liebner et al 2010) or N-methylmorpholine from NMMO, render it more stable, in complete agreement with general NMMO chemistry. There is one important exception: imidazole has a pronounced destabilizing effect in XMIm acetates (BMIM-OAc, EMIM-OAc).…”
mentioning
confidence: 64%
“…In particular, problems with recycling and byproduct accumulation have cast doubts on their general usefulness in biomass fractionation or pulping, as have literature accounts showing that these solvents undergo reactions with cellulose (Köhler et al 2007;Liebert et al 2009;Ebner et al 2008;Zweckmair et al 2015) and thus lack the inertness that is often claimed as one of benefits of ILs. Also thermal stress causes slow byproduct formation in XMim ionic liquids, mainly imidazole derivatives (Wendler et al 2012;Liebner et al 2010;Dorn et al 2008).…”
mentioning
confidence: 99%